Analysis of Shifts in Consumer Behavior in Fulfilling Clothing Needs: A Study of Online Shopping and MSME Tailoring Services in Petajen Village - Zukni, Aprilia Dwi Saputri; Saputri, Dea Amanda; Sentia, Deni Anes; Maulana, Dina; Arianti, Niken Dwi; Rifki, Ahmad (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The development of digital technology has transformed people’s consumption patterns from offline to online shopping, including in rural areas. This study aims to analyze shifts in consumer behavior in meeting clothing needs between online shopping and MSME tailoring services, as well as their impact on the sustainability of tailoring businesses in Petajen Village. This study employed a descriptive qualitative method, with data collected through semi-structured interviews involving MSME owners, employees, and consumers. The findings reveal that online shopping is preferred due to its ease of access, wide variety of products, relatively affordable prices, and promotional offers available on e-commerce platforms. However, local tailoring services still maintain a market segment for formal wear, family clothing, uniforms, bridesmaid dresses, as well as customization and size-adjustment services. The impact experienced by MSMEs is not only reflected in the decline of new clothing orders but also in the emergence of new opportunities, such as alteration services for clothing purchased online. The adaptation strategies implemented by MSMEs include utilizing social media, maintaining the quality of tailoring results, following fashion trends, and preserving personal relationships with customers. Thus, MSME tailoring services are not entirely replaced by e-commerce; instead, they have transformed into complementary services that rely on quality, size precision, and personalized customer service.